P PENGARUH PENGAWASAN KEDISIPLINAN KERJA TERHADAP PRODUKSI KARET PADA PT. PANTJA SURYA PERDAGANGAN - Rosintan Sipayung (Jurnal Ekonomi dan Bisnis (EK&BI), 2018)
The purpose of this study is to also learn how to influence supervision work discipline of the rubber production at PT. As for the issue of this research is "Is there any influence on the work discipline supervision rubber production at PT. Pantja Solar Trade "Data collection methods used in the study are as follows: a. Interview, b. Observation. Data analysis technique used in this research is to use the formula of product moment. This study population is all the production employees as many as 157 samples of this research are as many as 22 people. From simple linear regression coefficient is positive, meaning a positive relationship between the supervisory discipline with employee productivity, the higher the supervision of discipline (the lower absenteeism) then further increase employee productivity. Of correlation r value of 0.95 was obtained. What this means is that the relationship between the supervisory work discipline and productivity is very strong. Of unknown coefficient determination R2 values of (0.952) = 0, 9025. What this means is that the influence of discipline supervision variable to variable productivity of employees amounted to 90.25%. While the remaining 9.75% is influenced by other variables not included, such as in educational training, promotion and others.